2006
DOI: 10.1063/1.2163993
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of blood components on a surface in a microfluidic environment

Abstract: The aggregation of blood components on the blood-contacting surface of a medical device will reduce its reliability and lifetime. Such aggregations are known to be generated by sheared-flow activation of blood components which themselves are greatly influenced by flow patterns. This is especially important in the case of a microfluidic system. A numerical simulation was conducted to evaluate the flow parameters in a microminiature blood circulation loop to determine those flow factors that promote the aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Various proteins are expressed when platelets are activated by exposure to the damaged vessel wall, mediating and binding platelets to the wall. Activated platelets from the sequential functional response (adhesion, shape changing, release reaction, and aggregation) form a hemostatic plug that blocks the site of injury to prevent blood loss 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Various proteins are expressed when platelets are activated by exposure to the damaged vessel wall, mediating and binding platelets to the wall. Activated platelets from the sequential functional response (adhesion, shape changing, release reaction, and aggregation) form a hemostatic plug that blocks the site of injury to prevent blood loss 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…In these contexts observations of pattern-formation phenomena in microfluidic two-phase flows have been described [3][4][5][6]. We report a new such pattern that appears to be closely related to the well-known type of macroscopic sand-ripples [7][8][9][10][11] one finds on beaches or on the bottom of the ocean and rivers.…”
mentioning
confidence: 78%
“…The tube is connected to a Hamilton syringe (25 l) by means of a Teflon PTFE tube with an internal diameter of 300 m. The whole flow circuit is fully filled with water. The capillary tube contained approximately 5 l Duke Scientific polymer microspheres (diameter d G : 1 or 10 m; standard deviation from mean less than 5%; particle density G 1:05 g=cm 3 ). Microscopic inspection revealed that the system was free of entrapped air bubbles.…”
mentioning
confidence: 99%